THE ROLE OF TELEMEDICINE AND WEARABLE DEVICES IN HEALTHCARE DELIVERY AND PHYSICAL ACTIVITY PROMOTION: A NARRATIVE REVIEW - Marta Dziedziak; Michał Romaniuk; Julia Groszewska; Daria Julia Makowska-Woszczyk; Agata Rapior; Kinga Lubomska; Patrycja Jagura; Jan Romaniuk; Agata Mytych; Łukasz Nosek (International Journal of Innovative Technologies in Social Science, 2026)
Objective: This narrative review aims to evaluate the role of telemedicine and wearable devices in healthcare delivery and physical activity promotion, highlighting applications across multiple medical specialties and their impact on patient monitoring, rehabilitation, and chronic disease management. Methods: Relevant publications from 2018 to 2025 were retrieved from PubMed, Scopus, and Google Scholar. Included studies addressed the development, clinical utility, and behavioural impact of telemedicine platforms and wearable sensors within healthcare and exercise-related contexts. Key findings: Telemedicine and wearable devices are increasingly incorporated across diverse medical domains. In cardiovascular and sports medicine, they support exercise monitoring, early detection of physiological changes, and post-injury rehabilitation. In oncology and chronic disease management, these technologies enable remote symptom monitoring, adherence to therapy, and personalized care plans. Wearable devices provide continuous physiological data, enhancing individualized recommendations, safety, and motivation. Telemedicine contributes to promoting physical activity through real-time feedback and remote supervision. Limitations include device accuracy, data interpretation challenges, digital literacy barriers, and regulatory and privacy concerns. Future perspectives suggest hybrid care models and artificial intelligence integration to optimize monitoring and patient outcomes. Conclusion: Telemedicine and wearable technologies offer scalable, effective solutions for improving healthcare delivery and promoting physical activity. Their integration into clinical workflows, supported by hybrid models and equitable access strategies, has the potential to enhance monitoring, engagement, and overall health outcomes.